Mössbauer study of the effect of pH on Fe valence in iron–polygalacturonate as a medicine for human anaemia. (February 2015) - Kuzmann, E.; Garg, V.K.; de Oliveira, A.C.; Klencsár, Z.; Szentmihályi, K.; Fodor, J.; May, Z.; Homonnay, Z.
Abstract: Iron–polygalacturonate complexes have been synthesized from polygalacturonic acid by applying a novel preparation method in order to develop medicine suitable for the effective iron supplementation of the human body in the case of anemia. Since the iron uptake depends on the oxidation state of iron, 57 Fe Mössbauer spectroscopy was used to study the occurrence of different valence states in the iron–polygalacturonate complexes prepared under different circumstances. The Mössbauer-spectra indicated the presence of iron both in Fe II and Fe III states in the investigated iron–polygalacturonate compounds, the occurrence of which varied with the preparation parameters. A correlation of the relative occurrence of iron valence states with the pH has been found. The relative occurrence of Fe III was found to increase with increasing pH. The knowledge of this correlation can help find optimum preparation conditions of iron–polygalacturonates to cure human anemia. Highlights: Iron–polygalacturonates were synthesized at different pH using a novel preparation method. Mössbauer spectroscopy was used to study the effect of pH on Fe valence. We found nearly linear dependence of relative occurrence of Fe III with pH. The finding helps to optimize the preparation of iron–polygalacturonates as medicine for human anaemia.